Efektivitas Mikoriza Arbuskula dan Naungan pada Pertumbuhan Bibit Jati (Tectona grandis) - Delvian Delvian (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Effectiveness of Arbuscular Mycorhiza and Shanding in Growth of Teak SeedlingABSTRACT. Interaction between mycorrhizal inoculan dosage with level of shade was significantly affected of seedling growth of height, total dry weight matter, soot root ratio, P content, and degree of infected root by mycorrhizal. The usage of mycorrizal inoculants dosage at 10 g per seedling which combined with level of shade 75% gave the best for seedling growth of teak for siz moth old. Increasing level of shade 25% to 75% increased seedling growth of teak. Furthermore, seedling of teak that treated mycorrzal inoculants dosage at 100 g per seedling was more significantly affected of seedling growth than 5 g per seedling.